Measured thermal performance of a combined suspended particle switchable device evacuated glazing. (1st May 2016) - Ghosh, Aritra; Norton, Brian; Duffy, Aidan
Highlights: Test cell experiment is performed for a combined suspended particle switchable device evacuated glazing. The overall heat transfer coefficient this combined glazing has been calculated in both transparent and opaque state. The solar heat gain coefficient of this combined glazing has been calculated in both transparent and opaque state. The dynamic thermal behavior of glazing has been monitored. Abstract: A switchable suspended particle device (SPD) evacuated (vacuum) glazing has low inherent heat loss and can control solar heat gain by changing its transparency. The thermal performance of combined SPD–vacuum glazing has been investigated using a test cell. In this work two different combination of SPD– vacuum glazing was evaluated. In the first combination, SPD glazing was facing the outside ambient environment and vacuum glazing was facing the indoor test cell environment (SPD– vacuum). In the second combination, SPD glazing was facing the indoor test cell environment and vacuum glazing was facing the outdoor ambient environment (Vacuum–SPD). Variation of the SPD glazing position in a combined SPD–vacuum glazing had little impact on either the internal test cell temperature or the glazing surface temperature. This combined glazing system achieved a dynamic transmission range from 2% (opaque state) to 38% (transparent state). Low overall heat transfer coefficients between 1.00 W/m 2  K to 1.16 W/m 2  K were found for this combined glazing. Dynamic solar heat gain coefficient was possible using this glazing, which varied from 0.045 to 0.27. This type of combined glazing system is suitable for summer and winter both conditions.